A Quantitative Analysis of the Effects of Academic Supervision, Learning Community Engagement, and Teacher Motivation on Learning Quality Improvement in Ngaliyan District Elementary Schools, Semarang City - Rohbiyatun, Haidar; Kusumaningsih, Widya; Nurkolis (IJORER : International Journal of Recent Educational Research, 2025)
Objective: This study investigates the influence of academic supervision, learning community engagement, and teacher work motivation on learning quality in public elementary schools in Ngaliyan District, Semarang. The objective is to examine both the individual and combined contributions of these factors to the improvement of teaching and learning processes. Methods: A quantitative research design was employed, involving 187 teachers as respondents. Data were collected through structured questionnaires and analyzed using statistical techniques to determine the relative contributions of each variable. Results: The findings reveal that academic supervision contributes 68.1%, learning community engagement 62.6%, and teacher work motivation 67.8% to the improvement of learning quality. Collectively, these three variables explain 83.4% of the variance in learning quality, demonstrating their strong and interrelated effects. Novelty: This study provides empirical evidence on how academic supervision, collaborative professional communities, and teacher motivation jointly and individually enhance learning quality within the Indonesian elementary school context. The results offer practical insights for school leaders and policymakers in formulating strategies to strengthen supervision, foster collaborative learning communities, and enhance teacher motivation to achieve sustainable improvements in educational outcomes.